Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.analchem.8b04672
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Assay for Aminopeptidase Activity and Its Application for Dipeptidyl Peptidase-4 Drug Discovery

Abstract: Aminopeptidases, such as dipeptidyl peptidase-4 (DPP-4, CD26), are potent therapeutic targets for pharmacological interventions because they play key roles in many important pathological pathways. To analyze aminopeptidase activity in vitro (including high-throughput screening [HTS]), in vivo, and ex vivo, we developed a highly sensitive and quantitative bioluminescence-based readout method. We successfully applied this method to screening drugs with potential DPP-4 inhibitory activity. Using this method, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…In this part, d -cysteine is “caged” with DPP-4 specific recognition sequence of amino acids (Gly-Pro), resulting in a tripeptide Gly-Pro- d -Cys (GPc). Proteolytic activity of DPP-4 on this peptide enables the release of d -Cys and subsequent in situ formation of d -luciferin with HCBT . DPPIV is a transmembrane glycoprotein with proteolytic activity that is capable of cleaving N-terminal dipeptides from polypeptides with proline or alanine in the penultimate position. The DPPIV expression level variation was associated with various pathological processes, especially in diabetes and malignant tumors, implying that DPPIV was a potential biomarker for the early disease diagnosis and treatment .…”
Section: Resultsmentioning
confidence: 99%
“…In this part, d -cysteine is “caged” with DPP-4 specific recognition sequence of amino acids (Gly-Pro), resulting in a tripeptide Gly-Pro- d -Cys (GPc). Proteolytic activity of DPP-4 on this peptide enables the release of d -Cys and subsequent in situ formation of d -luciferin with HCBT . DPPIV is a transmembrane glycoprotein with proteolytic activity that is capable of cleaving N-terminal dipeptides from polypeptides with proline or alanine in the penultimate position. The DPPIV expression level variation was associated with various pathological processes, especially in diabetes and malignant tumors, implying that DPPIV was a potential biomarker for the early disease diagnosis and treatment .…”
Section: Resultsmentioning
confidence: 99%
“…The d -Cys moiety can be readily conjugated to existing Cys residues or introduced at the C-terminus or the N-terminus of the peptide chain, providing great flexibility and applicability of our method to a wide range of therapeutic peptides or proteins. To increase assay sensitivity, our efforts focused on lowering the high background noise resulting from endogenous l -Cys. , Despite the fact that a considerable number of studies have utilized the split luciferin approach for in vitro and in vivo applications, ,,, this problem had not yet been addressed . We found that quenching the background signal with excess CBT prior to treatment with SLP yields remarkable signal-to-noise ratios, with signals up to 60-fold greater than background levels even at low nanomolar concentrations of the peptide.…”
Section: Discussionmentioning
confidence: 98%
“…To increase assay sensitivity, our efforts focused on lowering the high background noise resulting from endogenous L-Cys. 28,48 Despite the fact that a considerable number of studies have utilized the split luciferin approach for in vitro and in vivo applications, 17,32,49,50 this problem had not yet been addressed. 50 We found that quenching the background signal with excess CBT prior to treatment with SLP yields remarkable signal-to-noise ratios, with signals up to 60-fold greater than background levels even at low nanomolar concentrations of the peptide.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations